SIDSTE PAS DE TROIS I GENÉVE: En dans for tre i FN’s saloner, hvor værten fører - Kvaale, Katja (Tidsskriftet Antropologi, 1996)
Katja Kvaale: Last pas de trois in Geneva: a dance for three in the UN saloons with the host leading the dance The purpose of this article is twofold. Taking its point of departure in empirical examples from the 1993 Session of the United Nations Working Group on Indigenous Populations in Geneva, the article attempts partly to analyse how indigenous peoples operate in the UN system, and partly to examine how this touches on classical anthropological notions such as peoplehood, nationhood and culture as distinet and continuous units. It is argued that most of the indigenous inputs at the UNWGIP can be heard as persistent reactions against the member states’ questioning their peoplehood and consequent rights to self-determination. However, it is not the idea to deconstruct the notion of the modem nation State altogether, nor to imply a radical cultural relativity, but rather to establish that the UN is confronting a global reality somewhat more complex than individuals and nation- states. In stating that the right to self-determination is separate from and prior to international law - it has been there since time immemorial - the indigenous representatives are tuming the legal logic of the UN upside down. From their perspective it is thus not a matter of being endowed with rights from a magnanimous UN, but rather a latecoming making up for the wrongdoings of half a millennium. Meanwhile, in asserting cultural continuity and distinetiveness in their politicized self-representation, indigenous peoples are catching anthropology off-guard and without foothold amidst the debris of its recently abandoned paradigms. Ironically, in the case of indigenous peoples the discipline is seemingly facing the incamation of the very notions and concepts just ditched: the exotification of the other, the radical us/them or West/the Rest distinetions, the Levi- Straussian „cold“ timelessness i.e. „conservative" rejection of modemity and development, culture as partly reified and self-sufficient units etc. However, rather than a morally based rejecting attitude towards this phenomenon the discipline would benefit from facing the great theoretical and analytical challenge that lies behind it. Although indigenous peoples and anthropologists are now operating within the same frame of reference to a far higher degree than was the case 25 years ago, it can still prove worthwhile to distinguish between the different levels on which culture is dealt with at different times. Hence, a potential clash between indigenous politieized „authentic culture" on the one hånd and scientific deconstruction of „true culture" on the other can be avoided.